2015
DOI: 10.1007/s00330-015-3697-0
|View full text |Cite
|
Sign up to set email alerts
|

ESR/ERS white paper on lung cancer screening

Abstract: Lung cancer is the most frequently fatal cancer, with poor survival once the disease is advanced. Annual low-dose computed tomography has shown a survival benefit in screening individuals at high risk for lung cancer. Based on the available evidence, the European Society of Radiology and the European Respiratory Society recommend lung cancer screening in comprehensive, quality-assured, longitudinal programmes within a clinical trial or in routine clinical practice at certified multidisciplinary medical centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
116
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 77 publications
0
116
0
7
Order By: Relevance
“…The most effective treatment for lung cancer is a surgery [4] but it requires an early diagnosis. In such stage, the cancer would be more likely to be treated successfully and generally would increase the chances of survival and improve the quality of life of the patients and the caregivers.…”
Section: Early Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The most effective treatment for lung cancer is a surgery [4] but it requires an early diagnosis. In such stage, the cancer would be more likely to be treated successfully and generally would increase the chances of survival and improve the quality of life of the patients and the caregivers.…”
Section: Early Diagnosismentioning
confidence: 99%
“…The study revealed that 24 countries [7] are responsible for approximately 97% of all lung cancer research articles published between 2004 and 2013 and although the number of papers published worldwide on this cancer has more than doubled from 2157 papers in 2004 to 4845 in 2013, the increase of the proportion of global research in lung cancer compared with other cancer types is minimal (4.4% in 2004, 5.6% in 2013). Apart from China, the research in most of other countries declined, particularly in Belgium, Poland, France, Norway, Italy, Spain, Greece and the Republic of Korea [8]. The majority of the research is dedicated to medicines, genetics and biomarkers, with less than 1% of it being dedicated to understand and improve palliative and support care and quality of life, despite the fact that many patients would benefit from early palliative care, given the poor survival rates with lung cancer [8].…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these task force reports, the ERJ also published a white paper on lung cancer screening that was jointly developed by the ERS and the European Society of Radiology [9].…”
mentioning
confidence: 99%
“…Recent data from the largest screening study, including more than 50 000 high-risk patients, shows benefit with lung cancer screening, while data from other studies are awaited [2]. The joint white paper published by the European Society of Radiology (ESR) and the European Respiratory Society (ERS) on lung cancer screening is not a general recommendation to perform lung cancer screening in Europe, but a recommendation on how to do it right and under what circumstances [3].According to the extensive review of all reported low-dose computed tomography (LDCT) lung cancer screening trials by SHLOMI et al [4] and the NELSON study data from the first three screening rounds, as discussed in the paper (and accompanying online supplementary material) by HOREWEG et al [5], the percentage of stage I lung cancer detected in prevalence screening rounds varies between 47.6% and 63.9% (if we omit the 81.8% of the LUSI trial). For the NELSON and NLST (National Lung Screening Trial) trials alone the percentage of stage I in the prevalence rounds were 64.9% and 58.3%, respectively [4,5].…”
mentioning
confidence: 99%